The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3892/or.2021.8169
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of circNRIP1 sensitizes colorectal cancer to 5‑FU via sponging miR‑532‑3p

Abstract: The present study aimed to investigate the influence of circular RNA nuclear receptor-interacting protein 1 (circNRIP1) on the chemotherapeutic effect of 5-fluorouracil (5-FU) in colorectal cancer (CRC) and reveal its potential molecular mechanisms. The effects of circNRIP1 on cell proliferation, migration and invasion, and apoptosis were evaluated using Cell Counting Kit-8, Transwell and flow cytometric assays, respectively. A dual-luciferase reporter assay was performed to verify the potential interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Among them, 19 were related to lymph node metastasis, 10 were related to distant metastasis, seven were related to both lymph node metastasis and distant metastasis, and the remaining six were related to liver metastasis ( Supplementary Table S7 ). There were 13 circRNAs associated with drug resistance, of which circDDX17 ( Ren et al, 2020 ), circ_0007031 ( He et al, 2020 ), circ_0032833 ( Li and Zheng, 2020 ), circ_0000338 ( Zhao et al, 2021 ), circNRIP1 ( Liu et al, 2021 ) were associated with 5-fluorouracil resistance; circ_0005963 ( Wang et al, 2020c ), circFBXW7 ( Xu et al, 2021 ) were associated with oxaliplatin resistance; circ_0000338 ( Hon et al, 2019 ), circ_32883 ( Abu et al, 2019 ) were associated with both 5-fluorouracil and oxaliplatin; circ_ 0020095 ( Sun et al, 2020 ), circ_0071589 ( Zhang et al, 2021b ), and circ_0131,663 ( Wang et al, 2021 ) were associated with cisplatin resistance; circCSPP1 ( Xi et al, 2021 ), and circ_0006174 ( Zhang et al, 2022 ) were associated with Adriamycin resistance. In addition, circ_0001313 was associated with radiotherapy resistance ( Wang et al, 2019a ) ( Supplementary Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 19 were related to lymph node metastasis, 10 were related to distant metastasis, seven were related to both lymph node metastasis and distant metastasis, and the remaining six were related to liver metastasis ( Supplementary Table S7 ). There were 13 circRNAs associated with drug resistance, of which circDDX17 ( Ren et al, 2020 ), circ_0007031 ( He et al, 2020 ), circ_0032833 ( Li and Zheng, 2020 ), circ_0000338 ( Zhao et al, 2021 ), circNRIP1 ( Liu et al, 2021 ) were associated with 5-fluorouracil resistance; circ_0005963 ( Wang et al, 2020c ), circFBXW7 ( Xu et al, 2021 ) were associated with oxaliplatin resistance; circ_0000338 ( Hon et al, 2019 ), circ_32883 ( Abu et al, 2019 ) were associated with both 5-fluorouracil and oxaliplatin; circ_ 0020095 ( Sun et al, 2020 ), circ_0071589 ( Zhang et al, 2021b ), and circ_0131,663 ( Wang et al, 2021 ) were associated with cisplatin resistance; circCSPP1 ( Xi et al, 2021 ), and circ_0006174 ( Zhang et al, 2022 ) were associated with Adriamycin resistance. In addition, circ_0001313 was associated with radiotherapy resistance ( Wang et al, 2019a ) ( Supplementary Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our study, many articles verify the influence of circRNAs dysregulation on CRC cell sensitivity to 5‐FU and enhances drug resistance. [ 29,30 ] For example, one study found that circ‐0000338 enhances 5‐FU resistance in CRC by negatively regulating miRNAs. [ 29 ] Another study found that circNRIP1 silencing sensitizes HCT116 and SW480 cells to 5‐FU by negatively regulating miR‐532‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] Another study found that circNRIP1 silencing sensitizes HCT116 and SW480 cells to 5‐FU by negatively regulating miR‐532‐3p. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, circRNAs are associated with drug resistance. In CRC, circNRIP1 [ 46 ] and circ_0000338 [ 47 ] confer 5-fluorouracil (5-FU) resistance and contribute to CRC progression, whereas circ_0082182 [ 48 ], hsa_circ_0005963 [ 49 ] and circATG4B [ 50 ] confer resistance to oxaliplatin.…”
Section: The Characteristics Of Glycolysis-associated Circrnas In Gi ...mentioning
confidence: 99%